2020
DOI: 10.3390/agronomy11010060
|View full text |Cite
|
Sign up to set email alerts
|

Tillage Practice Impacts on the Carbon Sequestration Potential of Topsoil Microbial Communities in an Agricultural Field

Abstract: Soil microorganisms are the core force driving the conversion of plant residues into soil organic carbon (SOC). Identifying the changes in soil microorganism responses to tillage practices is a key step in understanding the SOC sequestration potential. The aim of this study is to assess the impacts of different tillage practices on microbial communities and functions in agricultural soils. A field experiment involving no tillage (NT), rotary tillage (RT), and deep tillage (DT) in winter wheat-summer maize doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The results of this study indicated that the introduction of deep tillage into the C-RT could affect the availability of soil nutrients by changing the distribution of straw in soil, and increasing SOC in deep soil layers (Table 5). DT increased the composition of soil microorganisms and increased the transformation potential of straw-C to SOC [44]. Studies by Gomez-Rey [45] and Peixoto [21] showed the same result, namely, that occasional deep tillage changes soil texture, increases aeration and the uniform distribution of nutrients, thus increasing soil enzyme activity.…”
Section: Changes In Soil Physical Properties With Different Tillage P...mentioning
confidence: 71%
“…The results of this study indicated that the introduction of deep tillage into the C-RT could affect the availability of soil nutrients by changing the distribution of straw in soil, and increasing SOC in deep soil layers (Table 5). DT increased the composition of soil microorganisms and increased the transformation potential of straw-C to SOC [44]. Studies by Gomez-Rey [45] and Peixoto [21] showed the same result, namely, that occasional deep tillage changes soil texture, increases aeration and the uniform distribution of nutrients, thus increasing soil enzyme activity.…”
Section: Changes In Soil Physical Properties With Different Tillage P...mentioning
confidence: 71%
“…The soil microbial community is an important indicator of soil quality and tillage impacts soil microbes [4]. In this study, RTL exchanged the subsoil with the topsoil, after which the microbial groups of the different soil depths changed accordingly.…”
Section: Effects Of Restructuring Tilth Layers On Microbial Diversity...mentioning
confidence: 97%
“…Tillage plays a vital role in agricultural systems by providing suitable soil structure for seeds, repressing pests and weeds [2] and influencing crop root growth and yield [3]. Tillage not only improves the physical and chemical properties of soil, but also changes soil microbial communities [4,5]. Moreover, different tillage practices can promote the growth of microbes with different niches and alter the vertical distribution of soil microbial communities [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The soil microbial community is an important indicator of soil quality and tillage impacts soil microbes [29]. In this study, RTL exchanged the subsoil with the topsoil, after which the microbial groups at different soil depths changed accordingly.…”
Section: Effects Of Restructuring Tilth Layers On Microbial Diversity...mentioning
confidence: 97%